If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-4x-68=34-8x
We move all terms to the left:
5x-4x-68-(34-8x)=0
We add all the numbers together, and all the variables
5x-4x-(-8x+34)-68=0
We add all the numbers together, and all the variables
x-(-8x+34)-68=0
We get rid of parentheses
x+8x-34-68=0
We add all the numbers together, and all the variables
9x-102=0
We move all terms containing x to the left, all other terms to the right
9x=102
x=102/9
x=11+1/3
| (30-w)w=108 | | -10–8b=-10–12–9b | | -2=-(n-8 | | 5x-4/8=2 | | 2/5+x=3/10 | | 16x^2-16x+50=0 | | 1/2(8x-32)+16x=24 | | y=45(7)+30 | | x-5=6-5(x+7 | | -91+1x=91 | | 7/8(3d-2)=1/4(d+5) | | 19-6a-30=5 | | 10b+6=12b+18 | | n-6=6n-5 | | (x+5)(x-8)-(x+2)(x-9)=0 | | -15.61+5.8p+5p=12.8p+6.79 | | |x|-17=-21 | | 150-x-2=120+2x | | 11(k-1)=7(k-27) | | 7x+15-9x=5 | | 14x+34=2(17+7x | | m/4=m/12+2/3 | | -6=-k-1 | | 7x+5-x=41 | | 12d-10=11d-20 | | x/5+x/6=8/5 | | 192=2(2w+w) | | x2+6x-9=0 | | 26-9y=-1 | | -16z-(14z-2(z+3)-(2z+3))=-2z+9 | | 5k+12=-8k+2 | | -5/6a=5-8 |